ANALISIS TEKNIK DASAR SERVIS DAN PASSING BAWAH PERMAINAN BOLA VOLI PADA MAHASISWA PROGRAM STUDI PENJASKESREK UNVERSITAS SERAMBI MEKKAH - Bungsu Melia Sofya (CV Abid Abadi Jaya, 2026)
This study aimed to determine the level of basic technical skills in volleyball serving and underhand passing among students of the Physical Education, Health, and Recreation Study Program at Serambi Mekkah University. The research employed a quantitative approach with a descriptive design. The method used was a survey, with data collected through skill tests and measurements. The research instruments consisted of the AAHPER Serving Accuracy Test to measure serving ability and The Passing Test (Basic Passing Drill) to measure underhand passing ability. The sample included 15 students selected using a total sampling technique. The results showed that serving ability was distributed across several categories: 46.67% high, 13.33% moderate, 26.67% low, and 13.33% very low. Meanwhile, underhand passing ability demonstrated better outcomes, with 53.3% in the high category, 33.3% moderate, and 13.4% low. These findings indicate that students generally possess good underhand passing skills; however, serving ability still requires improvement. Therefore, structured and continuous training programs are needed to enhance serving accuracy while maintaining passing consistency